Emerging role of GLP-1 agonists in cardio-metabolic therapy - Focus on Semaglutide - Celestine Odigwe; Rajasekhar Mulyala; Haijra Malik; Brent Ruiz; Mariam Riad; Mohammad As Sayiadeh; Sanchitha Honganur; Alexis Parks; Mustafeez Ur Rahman; Nasser Lakkis (American Heart Journal Plus)
Semaglutide, a GLP-1 receptor agonist, has emerged as a promising agent in cardiovascular disease management, particularly for patients with obesity and diabetes. Recent studies have demonstrated significant benefits of Semaglutide beyond glycemic control, including reduced major adverse cardiovascular events (MACE), improvements in heart failure symptoms, and weight reduction. Notably, the STEP-HFpEF trial highlighted improved exercise capacity and a reduction in NT-proBNP levels, offering a novel therapeutic pathway for heart failure management. Additionally, Semaglutide has shown anti-inflammatory effects, reducing C-reactive protein (CRP) and tumor necrosis factor-alpha (TNF-α), thereby mitigating atherosclerotic risks. Moreover, the SELECT trial demonstrated Semaglutide's cardiovascular benefits in non-diabetic, obese patients, suggesting that its effects extend beyond weight loss. These findings represent a potential paradigm shift in cardiovascular risk management, although access and affordability remain key challenges.